Surgical implants in animal models for male and female infertility: A translational approach - S. Bharath; A.S. Vickram; B. Bhavani Sowndharya; C. Prasanth; D. Jenila Rani; G. Gulothungan; Hitesh Chopra; Tabarak Malik (Translational Research in Anatomy)
Structured Abstract: Background: Infertility remains a significant challenge in reproductive medicine, affecting both men and women. Recent advances in animal-based simulations of implant surgery have provided translational platforms for developing innovative reproductive therapies. Objectives: To review the role and progress of animal-based surgical implant models in enhancing gametogenesis, hormone production, and reproductive organ integrity, and to discuss their translational potential for treating infertility in men and women. Methods: In this review, animal model studies simulating implant surgeries for reproductive organs were analyzed to assess their potential in treating infertility. The investigation included a comprehensive review of advancements in microsurgical techniques, biological implants, and robotic-assisted procedures that enhance the precision and effectiveness of implant placement. Ethical guidelines governing preclinical development were also considered to ensure the suitability and safety of these approaches for future human application. Additionally, histopathological and genetic evaluations were examined as critical tools for optimizing implant design and function. Results: The results indicate that a broad spectrum of implants has been developed, ranging from autologous testicular and ovarian tissue grafts to artificial reproductive tissue scaffolds. In male infertility, testicular implants and prostheses designed for vasectomy reversal have demonstrated efficacy in restoring sperm production and addressing azoospermia. For female infertility, ovarian implants have been shown to support follicular growth, while fallopian tube and uterine prostheses facilitate embryo transfer and implantation. Technological advancements, including microsurgical and robotic assistance, have significantly improved the accuracy and success rates of these interventions. Preclinical studies have emphasized strict adherence to ethical standards and have utilized histopathological and genetic analyses to guide the refinement and optimization of these implants for clinical use. Conclusions: Surgical implants, when combined with assisted reproductive technologies, offer promising avenues for restoring fertility. However, clinical translation faces challenges related to biological compatibility and long-term function. Future research will focus on bioengineered constructs that integrate stem cells and smart biomaterials to further enhance therapeutic outcomes.